Approach to the Older Adult With Multiple Myeloma - Mina, Roberto (Am Soc Clin Oncol Educ Book, 2019)
Multiple myeloma (MM) is a disease of aging adults, and numerous therapeutic options are available for this growing demographic. MM treatment of older adults continues to evolve and includes novel combinations, new generations of targeted agents, immunotherapy, and increasing use of autologous stem cell transplantation (ASCT). Understanding age-related factors, independent of chronologic age itself, is an increasingly recognized factor in MM survivorship, especially in understudied populations, such as octogenarians. Octogenarians have inferior survival that cannot be explained by cytogenetic profiles alone. Incorporating assessments of geriatric factors can provide guidance on how to intensify or de-escalate therapeutic options. Functional status, using objective testing, is superior to traditional metrics of performance status and should be implemented to optimize the risk-benefit ratio of ASCT. ASCT is feasible and cost-effective, and chronologic age should not exclude ASCT eligibility. Upfront ASCT remains the standard of care, in the context of a sequential approach that includes pre-transplantation induction and post-transplantation maintenance. High-risk MM is classically defined by disease characteristics, yet shifting frameworks suggest that the high-risk designation could refer to any patient subgroup who is at risk for poorer outcomes—beyond disease-focused outcomes to patient-focused outcomes. Defining the optimal treatment of subgroups of older patients with high-risk disease on the basis of chromosomal abnormalities is unexplored. Here, we review tools to assess individual health status, explore vulnerability in octogenarians with MM, address ASCT decision-making, and examine high-risk MM to understand factors that contribute to survival disparities for older adults with MM.